SERTIFIKASI KOMPETENSI SEBAGAI UPAYA PERLINDUNGAN HUKUM BAGI TENAGA KERJA INDUSTRI PARIWISATA DALAM MENYAMBUT IATA - Ni Ketut Bagiastuti (Soshum: Jurnal Sosial dan Humaniora, 2014)
Workforce is the backbone of national development. This is because a strong workforce and highly competitive in many aspects will support increased development in the economic, social and culture and is a major factor for achieving success and strategic development of a nation. The government's responsibility to provide labor in sufficient quantity, time and place as well as the quality of appropriate skills. Because the purpose of the use of labor hire is intended as an attempt to employed labor force fully and productively. Competition labor demanding requirements of professional expertise and skills as evidenced by the certification of competence as one of the legal protection efforts undertaken by the government in welcoming IATA 2015.